1989
DOI: 10.1056/nejm198910053211402
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cigarette Smoking on Neutrophil Kinetics in Human Lungs

Abstract: Neutrophils may play a part in the pathogenesis of the centrilobular emphysema associated with cigarette smoking. The capillary bed of the lungs concentrates neutrophils approximately 100-fold with respect to erythrocytes, producing a large pool of marginated cells. We examined the effect of cigarette smoking on the kinetics of this pool of cells, using 99mTc-labeled erythrocytes to measure regional blood velocity and 111In-labeled neutrophils to measure the removal of neutrophils during the first passage thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
140
1
3

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(149 citation statements)
references
References 20 publications
5
140
1
3
Order By: Relevance
“…Long-lived ROS are either generated by phagocytic cells that accumulate in the pulmonary microcirculation in response to CS exposure (10,31) or originate from CS per se (12,13). CS gives rise to a wide array of ROS including superoxide and hydrogen peroxide, derived either from components of cigarette tar (i.e., the quinone/hydroquinone/ semiquinone system) or from the gas-phase, entertaining a steady state in which ROS are continuously formed and destroyed (12,13).…”
Section: Resultsmentioning
confidence: 99%
“…Long-lived ROS are either generated by phagocytic cells that accumulate in the pulmonary microcirculation in response to CS exposure (10,31) or originate from CS per se (12,13). CS gives rise to a wide array of ROS including superoxide and hydrogen peroxide, derived either from components of cigarette tar (i.e., the quinone/hydroquinone/ semiquinone system) or from the gas-phase, entertaining a steady state in which ROS are continuously formed and destroyed (12,13).…”
Section: Resultsmentioning
confidence: 99%
“…PMNLs in the marrow are larger and less deformable than those in peripheral blood [41], and when prematurely released are predisposed to sequestration in lung capillaries [20,28]. MACNEE et al [44] have shown that PMNLs are retained in the human lung by cigarette smoking, and recent studies by TERASHIMA et al [24] have shown that immature PMNLs are preferentially sequestered in lung microvessels. Assuming a cardiac output of 5 L .…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms by which cigarette smoke contributes to cardiovascular disease are not entirely understood, it has been demonstrated that cigarette smoke and its extracts induce diverse inflammatory events whose cumulative effects could contribute to cigarette smoke-related pathology. For example, cigarette smoke elicits the recruitment and adhesion of circulating leukocytes to the vessel wall (1)(2)(3), the initial step in inflammation (4, 5), emphysema (6), and atherosclerosis (7). Recruitment of leukocytes not only into the pulmonary microcirculation (6,8,9), but also into peripheral vascular beds such as the aorta and striated muscle (1,2), suggests that cigarette smoke elicits the formation of circulating inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cigarette smoke elicits the recruitment and adhesion of circulating leukocytes to the vessel wall (1)(2)(3), the initial step in inflammation (4, 5), emphysema (6), and atherosclerosis (7). Recruitment of leukocytes not only into the pulmonary microcirculation (6,8,9), but also into peripheral vascular beds such as the aorta and striated muscle (1,2), suggests that cigarette smoke elicits the formation of circulating inflammatory mediators. Indeed, monocytes isolated just after smoking are in an activated state (10) and plasma isolated just after smoking activates platelets isolated from nonsmokers (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation